2021
DOI: 10.3390/biom11030436
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous 3,3′-Diindolylmethane Improves Vanadium Stress Tolerance in Brassica napus Seedling Shoots by Modulating Antioxidant Enzyme Activities

Abstract: 3,3′-diindolylmethane (DIM) belongs to a family of indole glucosinolate compounds that have been shown to improve Brassica napus growth through the modulation of reactive oxygen species when applied exogenously. The B. napus cultivar AV Garnet was previously identified as a vanadium-sensitive cultivar. Therefore, in this study we investigated whether exogenous DIM could improve the vanadium tolerance of AV Garnet. We performed the following experiments: seed germination assessment, dry weight assessment, cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 70 publications
(60 reference statements)
4
6
0
Order By: Relevance
“…Therefore, we hypothesize that the chlorophyll b improvement by MG under the Zr stress could be as an indirect stress only regulation which is only induced under stress conditions. In a previous study, we also observed the same indirect regulation of chlorophyll b by signaling molecule 3,3′-diindolylmethane (DIM) under vanadium (V) stress in B. napus 18 which supports our hypothesis. The increase in Zr content could have led to a reduction of magnesium (Mg) ions which could also explain the reduction observed.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…Therefore, we hypothesize that the chlorophyll b improvement by MG under the Zr stress could be as an indirect stress only regulation which is only induced under stress conditions. In a previous study, we also observed the same indirect regulation of chlorophyll b by signaling molecule 3,3′-diindolylmethane (DIM) under vanadium (V) stress in B. napus 18 which supports our hypothesis. The increase in Zr content could have led to a reduction of magnesium (Mg) ions which could also explain the reduction observed.…”
Section: Discussionsupporting
confidence: 87%
“…However, the concentrations of O 2 •− , H 2 O 2 and · OH have never been measured in MG-only treated plants. Nonetheless, we hypothesize that MG increases O 2 •− and H 2 O 2 for signaling purposes and our hypothesis is supported by Gokul et al 18 which observed increases in O 2 •− and H 2 O 2 but not · OH in B. napus in response to DIM. In our study, exogenous MG led to an endogenous increase in MG and this was also observed in Zea mays by Wang et al 39 .…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…However, the effect of this compound on improving plant yield under stress has been less considered. Some studies have shown that the application of exogenous antioxidant compounds in activating the plant defense system against many stresses such as heavy metals (Sharma et al, 2021;Gokul et al, 2021), cold (Oz dan-Konakci et al, 2019 and salinity stress (Idrees et al, 2011;Azooz et al, 2013;Liu et al, 2016;Oz dan-Konakci et al, 2020). Recently, Oz dan- showed the involvement of naringenin in the improvement of growth and increment of osmotic adjustment on salt (100 mM NaCl)-stressed Phaseolus vulgaris.…”
Section: Introductionmentioning
confidence: 99%